2020
DOI: 10.20944/preprints202010.0039.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tunneled Peritoneal Catheter for Refractory Ascites in Cirrhosis: A Randomized Case-Series

Abstract: Background and objectives: Refractory ascites markedly worsens prognosis in cirrhosis. Large volume paracentesis (LVP) is standard treatment, but complications are common. In a randomized controlled case-series, we assessed a permanent tunneled peritoneal catheter versus LVP in patients with cirrhosis and ascites. Materials and Methods: Random allocation was computer-generated, and concealment used opaque envelopes. Patients were included from 01-2017 to 12-2018. Inclusion criteria were cirrhosis and recurrent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Two studies have attempted to address this issue using a randomised trial design but both were terminated early. 6,7 One study was published and reported a high risk of peritonitis when patients in the permanent catheter group were assessed in a systematic fashion. 7 The large retrospective study by Tergast et al evaluated the use of permanent tunnelled catheters (PleurX™).…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have attempted to address this issue using a randomised trial design but both were terminated early. 6,7 One study was published and reported a high risk of peritonitis when patients in the permanent catheter group were assessed in a systematic fashion. 7 The large retrospective study by Tergast et al evaluated the use of permanent tunnelled catheters (PleurX™).…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…6,7 One study was published and reported a high risk of peritonitis when patients in the permanent catheter group were assessed in a systematic fashion. 7 The large retrospective study by Tergast et al evaluated the use of permanent tunnelled catheters (PleurX™). 8 The PleurX is not approved for non-malignant ascites.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 1 more Smart Citation